2011
DOI: 10.1159/000329572
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Orbital Volume of Korean People in Their 20s or 40s

Abstract: Aims: To measure the orbital volume of normal Korean people in two different age groups (subjects were in their 20s or 40s), and analyze the differences of orbital volume with respect to age and gender. In addition, to analyze correlation between body parameters (height and weight) and the orbital volume. Methods: Magnetic resonance imaging (MRI) data were acquired for a total of 143 subjects, consisting of 71 subjects in their 20s (32 males and 39 females) and 72 subjects in their 40s (30 males and 42 females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…In this study, the mean OV of Chinese adult males was 22 ± 2.2 cm 3 , which was significantly higher than that of females (20 ± 1.5 cm 3 ). Previous studies have demonstrated that the OV data in Asians, such as Hong Kong people in China (male: 22 ± 1.4 cm 3 ; female: 20 ± 2.2 cm 3 ) [10] and Koreans (22 ± 1.7 cm 3 for men and 19 ± 1.8 cm 3 for women) [11], were similar to ours. However, among Caucasians, the OVs (29 ± 2.4 cm 3 for males and 25 ± 2.2 cm 3 for females) [7] were greater than those for the population in this study.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, the mean OV of Chinese adult males was 22 ± 2.2 cm 3 , which was significantly higher than that of females (20 ± 1.5 cm 3 ). Previous studies have demonstrated that the OV data in Asians, such as Hong Kong people in China (male: 22 ± 1.4 cm 3 ; female: 20 ± 2.2 cm 3 ) [10] and Koreans (22 ± 1.7 cm 3 for men and 19 ± 1.8 cm 3 for women) [11], were similar to ours. However, among Caucasians, the OVs (29 ± 2.4 cm 3 for males and 25 ± 2.2 cm 3 for females) [7] were greater than those for the population in this study.…”
Section: Discussionsupporting
confidence: 86%
“…Similar gender variation was noted in other studies [1,5,[12][13][14][15][16][17][18]. Bentley et al [10] used MRI to measure OV of mainly Caucasians and found that OV was larger in British children compared to Saudi children.…”
Section: Discussionsupporting
confidence: 75%
“…One CT study on Chinese patient conducted by Ji, et al defined an anterior limit including the entire globe and eyelid tissue [ 7 ]. Possibly due to the extra-orbital contents, their results approximated those of Caucasian populations (28.41±2.09 ml) and were higher than a number of studies in Asian populations ( Table 3 ) [ 6 , 8 , 9 , 21 ]. The study on Hong Kong Chinese patients by Chau et al utilized MRI images for orbital volume calculation.…”
Section: Discussionmentioning
confidence: 52%